Μ-metal magnetic cavities for polarization and maintenance of polarization of 3He gas. (October 2019) - Babcock, Earl; Salhi, Zahir; Barnsley, Lester; Voigt, Jörg; Mattauch, Stefan; Ioffe, Alexander
Abstract: Low gradient magnetic holding fields are required for maintaining the polarization of polarized 3 He, as diffusion though non-ideal gradients can cause total relaxation rates much greater than the intrinsic total 3 He relaxation rate of a particular 3 He cell in optimal conditions. For neutron scattering applications we often rely on µ -metal cavities to provide a degree of shielding from the many other sources of magnetic fields and gradient experienced on a typical neutron instrument. The JCNS utilizes two concepts for such cavities, one based on inexpensive plastic-bonded magnets to provide magnetic flux, and the other based on field coils wound on the sides of the µ -metal cavity. 2 different sized of permanent magnet cavities and three different geometries of coil-based cavities have been produced. Both types of boxes will be presented with magnetic design as well as mechanical construction details along with the achieved performance of the constructed devices.